Peningkatan Pengetahuan Akuntansi Dasar pada Guru-guru SMK Sumatra 40 Bandung - Bayunitri, Bunga Indah; Brata, Ignatius Oki Dewa; Laksono, Roosaleh; Heru, Yogo; Gunanta, Remon; Gusnandar, Sendi (Kreativasi : Journal of Community Empowerment, 2024)
Community service activities for Teachers at Vocational School Sumatra 40 Bandung aim to optimize teachers who want to update their Basic Accounting Knowledge. It also helps to improve their basic accounting skills by expanding the marketing they gain after understanding basic accounting knowledge. The role of Basic Accounting Knowledge today is not only the ability to calculate, record, and make financial reports but also to provide new understanding and knowledge that students need. It is hoped that students will gain new knowledge that can be applied in the world of work so as to produce more competitive graduates. At the start of updating Basic Accounting knowledge, a solution is needed to resolve a series of problems, namely training in basic Accounting Knowledge, such as understanding the philosophy of assets, liabilities, and equity. From these three materials, it is hoped that you will have a good mastery of assets, liabilities, and equity. This update is also needed to be transferred to students facing accounting problems they will encounter in the world of work. As a result of this activity, the teachers at SMK Sumatra 40 Bandung have implemented financial management in every unit in the school, which becomes an example of implementation for their students.